Critical Analysis of a Population Mental Health Strategy: Effects on Stigma for People With Intellectual and Developmental Disabilities. Issue 2 (3rd April 2017) - Hamdani, Yani; Ary, Ayelet; Lunsky, Yona
ABSTRACT: Introduction : Stigma is widely identified as an issue affecting the health and well-being of people with intellectual and developmental disabilities (IDD), and those with mental illnesses. To address this issue, a population mental health strategy, which includes a focus on reducing stigma and discrimination, was developed by the government of Ontario, Canada. Methods : Drawing on a critical policy analysis approach, we examined how stigma and mental illness are problematized and addressed in this strategy, and the implications for people with co-occurring IDD and mental illness. Results : Our analysis revealed that implicit understandings of exclusion, dependency, and inadequate economic participation have shaped how the explicitly identified issues of stigma and discrimination related to mental illness are problematized in the strategy. These implicit understandings have shaped courses of action (e.g., mental health promotion and anti-stigma programs) that may have positive consequences (e.g., skills for managing one's own mental health, decreased discrimination related to mental illness), but may have unintended negative consequences (e.g., stigma of being different and doing different than people without IDD and/or mental illness, and not being able to support oneself). Conclusions : Acknowledging disability discrimination and emphasizing other ways of participating and being included in communities that are not predominantly focused on independence and productivity can potentially contribute to reducing the stigma experienced by people with concurrent IDD and mental illness, and improve their health and well-being.